The Effect of Legal Awareness, Access to Justice, and Social Support on Legal Compliance Behavior in MSMEs in Jakarta - Hendri Khuan; Loso Judijanto; Arief Fahmi Lubis (West Science Social and Humanities Studies, 2024)
This research investigates the influence of legal awareness, access to justice, and social support on legal compliance behavior within Micro, Small, and Medium Enterprises (MSMEs) in Jakarta. Utilizing a quantitative approach with a sample of 150 businesses, the study employs Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze the relationships between the key constructs. The results reveal significant positive associations between legal awareness, access to justice, social support, and legal compliance behavior. The findings emphasize the importance of legal education, improved access to justice, and supportive networks in fostering a culture of compliance among MSMEs. The study contributes to the understanding of factors influencing legal behavior in the context of small businesses and provides practical implications for policymakers, business support organizations, and MSME stakeholders.